Design and Implementation of IP-based RFID Location Systems - Phuoc-Nguyen Tran (Journal of Communications Software and Systems, 2009)
Designing an IP-based RFID system allows low costdeployment and easy integration with IP-based services. In this paper, we propose an IP-based RFID architecture and focus on location management which allows determining “where” the object is after moving. The IP-based RFID architecture includes several components that allow collecting information from RFID infrastructure and updating the current location of RFID tags. A SIP-based implementation is proposed to validate the proposed architecture.